2020
DOI: 10.1155/2020/6090354
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 1-Methylcyclopropene in the Regulation of Antioxidative System and Softening of Mango Fruit during Storage

Abstract: The function of 1-methylcyclopropene (1-MCP) in the regulation of quality and antioxidative system of mango fruit was investigated during storage at ambient temperature. Changes in fruit quality, colour, ethylene production, respiration rate, fruit softening enzyme activities, and antioxidative enzyme activities were studied in this study. The results demonstrated that 1-MCP was beneficial for maintaining quality. 1-MCP treatment retarded the decline of firmness, weight, total soluble solid, and titratable aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
4
7
0
Order By: Relevance
“…wrapping treatments (T1, T2, T3 and T4) Moreover lowest yellow colour development was observed at 1-MCP 0.5 and 1.0 µL L -1 and those treatments were significantly different from the rest. Present findings are in agreement with Li et al (2020) that reported good effect of 1-MCP on mango peel colour.…”
Section: Titratable Acidity (Ta)supporting
confidence: 94%
“…wrapping treatments (T1, T2, T3 and T4) Moreover lowest yellow colour development was observed at 1-MCP 0.5 and 1.0 µL L -1 and those treatments were significantly different from the rest. Present findings are in agreement with Li et al (2020) that reported good effect of 1-MCP on mango peel colour.…”
Section: Titratable Acidity (Ta)supporting
confidence: 94%
“…The defense system protects cells from oxidative damage by preventing the accumulation of free oxygen radicals [23,42]. In previous studies, similar to the current study, it was determined that CAT, SOD, and APX enzyme activity was higher in 1-MCP-treated fruit, while MDA content was lower than in control fruit [43][44][45]. In general, during the ripening of red tomatoes, chlorophyll molecules are degraded by enzymes, and the green color disappears on the fruit skin [6].…”
Section: Discussionsupporting
confidence: 81%
“…Another possibility is that growth regulator treatments obstruct ethylene action and delay ripening, which increases the resistance of fruit to decay (since cell wall disassembly and tissue softening during postharvest ripening makes the fruit more susceptible to pathogen infection and increases the incidence of decay) (Cantu et al 2008; Lacerna et al 2018; Fan et al 2018; Błaszczyk and Gasparski 2019; Li et al 2020).The activity of PPO and POD was affected by 1-MCP, NAA, and AVG treatments. These results are con rmed by those ofLi et al (2020) andZhang et al (2020), who noted that 1-MCP inhibits the activities of enzymes (such as POD and PPO) related to cell wall degradation, fruit browning, and ethylene biosynthesis; particularly, 1-MCP was shown to maintain rmness and extension the post-harvest life in mango fruit. Additionally, phenolic compounds act as substrates for oxidizing enzymes, which can turn fruit tissues brown during handling, processing, and manipulation.…”
supporting
confidence: 72%